Potency of Young Coconut Water as a Mouthwash to Saliva pH and Flow Rate in Smokers - Yunita P. D. Nurazizah; Dian Lesmana; Silvi Kintawati (e-GiGi, 2022)
Abstract: Smoking causes harmful effects on health, especially the oral cavity. However, the oral cavity has saliva as a defence system that can eliminate harmful substances from the body. Normally saliva secreted by the salivary glands has a pH of 6.7-7.4 while in smokers the pH tends to be more acidic. This study aimed to determine the potential of coconut water as a natural mouthwash on the pH and salivary flow in smokers. This was a literature review study by searching scientific journals in Indonesian and English from 2019-2020 through search engines at SINTA, PubMed, and Google Scholar. The keywords used were young coconut water, gargling, cigarette, salivary flow rate, smoking, and salivary pH. The results obtained 17 suitable articles. Individuals who smoked more than 10 cigarettes/day, more than 6 years could have decreased pH and salivary flow. Therefore, coconut water was needed to reduce its effect, which was believed could increase pH and salivary flow. Coconut water had a pH that was almost the same as normal pH of saliva, which was 7.3. Coconut water contained tannins which gave a bitter taste, therefore, it stimulated salivary secretion and increased pH and salivary flow. In conclusion, young coconut water has a pH which is similar with normal saliva, therefore, it could become a natural potential mouthwash to increase pH and salivary flow in smokers. Keywords: young coconut water; mouthwash; salivary flow rate; smoking; salivary pH Abstrak: Merokok memberikan efek berbahaya bagi kesehatan terutama rongga mulut karena mengandung kurang lebih 5000 bahan kimia yang berbahaya. Rongga mulut memiliki saliva sebagai sistem pertahanan yang dapat mengeliminasi zat berbahaya dari tubuh. Cairan saliva disekresikan oleh kelenjar saliva 0,5-1,5 liter/hari dengan pH 6,7-7,4 sedangkan pH pada perokok cenderung lebih asam. Penelitian ini bertujuan untuk mengetahui potensi air kelapa sebagai cairan kumur alami terhadap pH dan aliran saliva perokok. Metode penelitian berupa literature review dengan mencari jurnal ilmiah berbahasa Indonesia dan Inggris dari tahun 2019-2020 melalui mesin pencarian di SINTA, PubMed, dan google scholar dengan kata kunci: air kelapa muda, berkumur, laju aliran saliva, merokok, pH saliva, rokok. Hasil pencarian mendapatkan 17 artikel yang sesuai. Individu yang merokok lebih dari 10 batang/hari lebih dari enam tahun dapat mengalami penurunan pH dan aliran saliva. Dibutuhkan upaya untuk menguranginya, salah satunya dengan berkumur menggunakan air kelapa, yang diyakini dapat meningkatkan pH dan aliran saliva. Hal ini terjadi karena air kelapa memiliki pH yang sama seperti pH normal yaitu 7,3. Air kelapa mengandung tannin yang memberikan rasa pahit sehingga merangsang sekresi saliva yang dapat meningkatkan pH dan aliran saliva. Simpulan penelitian ini ialah air kelapa mempunyai pH mendekati pH saliva normal sehingga dapat menjadi potensi alami untuk meningkatkan pH dan laju aliran saliva pada perokok. Kata kunci: air kelapa muda; berkumur; laju aliran saliva; merokok; pH saliva